House of skin - Jonathan Janz
Myles Carver is dead. But his estate, Watermere, lives on, waiting for a new Carver to move in. Myles's wife, Annabel, is dead too, but she is also waiting, lying in her grave in the woods. For nearly half a century she was responsible for a nightmarish reign of terror, and she's not prepared to stop now. She is hungry to live again-- and her unsuspecting nephew, Paul, will be the key. Who could imagine that what was once a moldering corpse in a forest grave is growing stronger every day, eager to take her rightful place amongst the horrors of Watermere? Read less